TRANSFORM (Multicenter Experience With Rapid Deployment Edwards INTUITY Valve System for Aortic Valve Replacement) US clinical trial: Performance of a rapid deployment aortic valve - Barnhart, Glenn R.; Accola, Kevin D.; Grossi, Eugene A.; Woo, Y. Joseph; Mumtaz, Mubashir A.; Sabik, Joseph F.; Slachman, Frank N.; Patel, Himanshu J.; Borger, Michael A.; Garrett, H. Edward Jr.; Rodriguez, Evelio; McCarthy, Patrick M.; et al. (My University, 2017)
Background: The TRANSFORM (Multicenter Experience With Rapid Deployment Edwards INTUITY Valve System for Aortic Valve Replacement) trial (NCT01700439) evaluated the performance of the INTUITY rapid deployment aortic valve replacement (RDAVR) system in patients with severe aortic stenosis. Methods: TRANSFORM was a prospective, nonrandomized, multicenter (n 1⁄4 29), single-arm trial. INTUITY is comprised of a cloth-covered balloon- expandable frame attached to a Carpentier-Edwards PERIMOUNT Magna Ease aortic valve. Primary and effectiveness endpoints were evaluated at 1 year. Results: Between 2012 and 2015, 839 patients underwent RDAVR. Mean age was 73.5 8.3 years. Full sternotomy (FS) was used in 59% and minimally invasive surgical incisions in 41%. Technical success rate was 95%. For isolated RDAVR, mean crossclamp and cardiopulmonary bypass times for FS were 49.3 26.9 minutes and 69.2 34.7 minutes, respectively, and for minimally invasive surgical 63.1 25.4 minutes and 84.6 33.5 minutes, respectively. These times were favorable compared with Society of Thoracic Surgeons data- base comparators for FS: 76.3 minutes and 104.2 minutes, respectively, and for minimally invasive surgical, 82.9 minutes and 111.4 minutes, respectively (P<.001). At 30 days, all-cause mortality was 0.8%; valve explant, 0.1%; throm- boembolism, 3.5%; and major bleeding, 1.3%. In patients with isolated aortic valve replacement, the rate of permanent pacemaker implantation was 11.9%. At 1 year, mean effective orifice area was 1.7 cm2; mean gradient, 10.3 mm Hg; and moderate and severe paravalvular leak, 1.2% and 0.4%, respectively.